Pengaruh Pembayaran Tunai Dan Non Tunai Terhadap Motivasi Kerja Driver Grab Di Kota Malang - Brahmantyo Yudistira; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims is for describe about cash, non-cash payments, and work motivation of GRAB drivers in Malang city, and to determine the effect of the payment methods used by consumers which have an impact on Work Motivation. This research was conducted at GRAB Drivers who the office at Laksda Adi Sucipto street number 53, Blimbing, Malang City. With a sample number of respondents is 99 driver. The data analysis technique uses multiple linear regression analysis.The results of descriptive analysis is the GRAB Driver in Malang City perceives if cash and non-cash payments are the same as increasing the work motivation of GRAB Drivers in Malang City. However, the impact of cash and non-cash payments is different. Based on the regression coefficient value, it can be seen that the coefficient of the non-cash payment variable is greater than the coefficient of the cash payment variable. This indicates that non-cash payments have more effect on the work motivation of the GRAB Driver than cash payments. Keywords: Cash Payments, Non Cash Payments and Work Motivation